P089 Detection of Neisseria gonorrhoeae bacterial loads in the pharynx and saliva among men who have sex with men. (30th June 2016) - Chow, Eric; Tabrizi, Sepehr; Phillips, Samuel; Lee, David; Bradshaw, Catriona; Chen, Marcus; Fairley, Christopher
Abstract : Background/introduction: Studies have shown that N. gonorrhoeae can be cultured in human saliva among individuals with pharyngeal gonorrhoea. As saliva could potentially act as a carrier for gonorrhoea transmission during sex, the bacterial load of N. gonorrhoeae in saliva may influence the transmissibility of gonorrhoea. Aim(s)/objectives: To quantify the gonococcal bacterial load in the pharynx and saliva among men who have sex with men (MSM) with untreated pharyngeal gonorrhoea. Methods: MSM who tested positive for pharyngeal gonorrhoea by culture were recalled for antibiotic treatment within 14 days between October 2014 and March 2015. The gonococcal bacterial load was estimated using real-time quantitative PCR (qPCR) by interpolating against a standard curve generated with known gonococcal DNA copy numbers. The median of gonococcal bacterial load in the pharynx and saliva was calculated and compared between culture positivity using Mann-Whitney U test. Results: A total of 33 men were included in this study. At the time of treatment, the median gonococcal bacterial load in the pharynx was similar in men who were culture-positive (2.5 × 10 5 copies/swab) and culture-negative (2.9 × 10 4 copies/swab) ( p = 0.166), and similar in the saliva in culture-positive: 2.2 × 10 5 copies/ml compared to culture-negative: 2.7 × 10 5 copies/ml samples ( p = 0.499). Discussion/conclusion: The gonococcal bacterial loads were similar between saliva and the pharynx and not influenced by culture status. Saliva could be important in the transmission of gonorrhoea such as oral-anal sex and saliva use as a lubricant for anal sex.